Ethical governance model for the data economy ecosystems - Koskinen Jani; Knaapi-Junnila Sari; Helin Ari; Rantanen Minna Marjaana; Hyrynsalmi Sami (EMERALD GROUP PUBLISHING LTD, 2025)
Purpose
Data economy is a recent phenomenon, raised by digital transformation and platformisation, which has enabled the concentration of data that can be used in economic purposes. However, there is a lack of clear procedures and ethical rules on how data economy ecosystems are governed. As a response to the current situation, there has been criticism and demands for the governance of data use to prevent unethical consequences that have already manifested. Thus, ethical governance of the data economy ecosystems is needed. The purpose of this paper is to introduce a new ethical governance model for data economy ecosystems. The proposed model offers a more balanced solution for the current situation where a few global large-scale enterprises dominate the data market and may use oligopolistic power over other stakeholders.
Design/methodology/approach
This is a conceptual article that covers theory-based discourse ethical reflection of data economy ecosystems governance. The study is based on the premise of the discourse ethics where inclusion of all stakeholders is needed for creating a transparent and ethical data economy.
Findings
This article offers self-regulation tool for data economy ecosystems by discourse ethical approach which is designed in the governance model. The model aims to balance data "markets " by offering more transparent, democratic and equal system than currently.
Originality/value
By offering a new ethically justified governance model, we may create a trust structure where rules are visible and all stakeholders are treated fairly.